Associations of Multimodal Analgesia With Postoperative Pain Trajectories and Morphine Consumption After Hepatic Cancer Surgery - Yeh, Chia-Yi; Chang, Wen-Kuei; Wu, Hsiang-Ling; Chau, Gar-Yang; Tai, Ying-Hsuan; Chang, Kuang-Yi (Frontiers in Medicine, 2022)
Background: This study aimed to investigate the influential factors of postoperative pain trajectories and morphine consumption after hepatic cancer surgery with particular interest in multimodal analgesia. Methods: Patients receiving hepatic cancer surgery at a tertiary medical center were enrolled between 2011 and 2016. Postoperative pain scores and potentially influential factors like patient characteristics and analgesic used were collected. Latent curve analysis was conducted to investigate predictors of postoperative pain trajectories and linear regression model was used to explore factors associated with postoperative morphine consumption. Results: 450 patients were collected, the daily pain scores during the first postoperative week ranged from 2.0 to 3.0 on average. Male and higher body weight were associated with more morphine consumption (both p < 0.001) but reduced morphine demand was noted in elderly (p < 0.001) and standing acetaminophen users (p = 0.003). Longer anesthesia time was associated with higher baseline pain level (p < 0.001). In contrast, male gender (p < 0.001) and standing non-steroidal anti-inflammatory drugs (NSAIDs) use (p = 0.012) were associated with faster pain resolution over time. Conclusions: Multimodal analgesia with standing acetaminophen and NSAIDs had benefits of opioid sparing and faster pain resolution, respectively, to patients receiving hepatic cancer surgery.